MOB1 regulates thymocyte egress and T‐cell survival in mice in a YAP1‐independent manner. (24th May 2019) - Kato, Wakako; Nishio, Miki; To, Yoko; Togashi, Hideru; Mak, Tak Wah; Takada, Hidetoshi; Ohga, Shouichi; Maehama, Tomohiko; Suzuki, Akira
Abstract: Mammalian STE20‐like protein kinase 1/2 (MST1/2) and nuclear Dbf2‐related kinase 1/2 (NDR1/2) are core components of Hippo signaling that are also known to be important regulators of lymphocyte trafficking. However, little is understood about the roles of other Hippo pathway molecules in these cells. Here, we present the first analysis of the function of Mps one binder kinase activator‐1 (MOB1) in T lymphocytes in vivo . T‐cell‐specific double knockout (DKO) of MOB1A/B in mice [t Mob1 DKO mice] reduces the number of naïve T cells in both the circulation and secondary lymphoid organs, but leads to an accumulation of CD4 + CD8 − and CD4 − CD8 + single‐positive (SP) cells in the thymus. In vitro, naïve MOB1A/B‐deficient T cells show increased apoptosis and display impaired trafficking capacity in response to the chemokine CCL19. These defects are linked to suppression of the activation of MST and NDR kinases, but are independent of the downstream transcriptional co‐activator Yes‐associated protein 1 (YAP1). Thus, MOB1 proteins play an important role in thymic egress and T‐cell survival that is mediated by a pathway other than conventional Hippo‐YAP1 signaling. Abstract : In this study, we present the first analysis of the function of MOB1 in T lymphocytes in vivo . T‐cell‐specific double knockout of MOB1A/B in mice reduces the number of naïve T cells.